Application of the world leading countries armies experience to improve the vocational military personnel training system - Oliynik, L. V. (Honor and Law, 2019)
The vocational military personnel training system in the world leading armies as a basic constituent of officer training is considered. Ways for completion the tasks of the military education system in the Armed Forces of Ukraine on the basis of experience of the vocational military personnel training system in foreign armies are defined.